Electrical Conduction in (Na0.5Bi0.5)1−xBaxTiO3 (0≤x≤1) Ceramic by Complex Impedance/Modulus Spectroscopy. (21st March 2013) - Roy, Ansu Kumar; Prasad, Kamal; Prasad, Ashutosh
Abstract : The present work describes the piezoelectric, impedance, and conductivity studies of ( Na 0 .5 Bi 0 .5 ) 1 − x Ba x TiO 3 ; ( 1 - x ) BNT-x BT ( 0 ≤ x ≤ 1 ) ceramics. The ceramics were prepared by conventional ceramic fabrication technique. X-ray diffraction data confirmed the formation of a pure compound in all the compositions. Williamson-Hall plot yielded the apparent crystallite sizes 26–52 nm, and SEM micrograph showed grain sizes ranging between 1.8–3.5 μ m for the material samples. Values of longitudinal piezoelectric charge coefficients of the samples poled under a dc electric field of about 2.5 kV/mm at 80°C/15 min indicated that their piezoelectric properties near the MPB are rather sensitive to the phase composition and reach preferred values at x = 0.08, where the relative content of the tetragonal phase is significantly higher than that of the monoclinic phase. Complex impedance/modulus spectroscopic analyses indicated the presence of grain-boundary effect along with the bulk contribution and also confirmed the presence of non-Debye type of multiple relaxations in the materials. The temperature dependent electrical conductivity data suggest the negative temperature coefficient of resistance behaviour. The activation energy studies allow insight into the nature of the conduction mechanisms occurring in the materials system which are explained on the basis of hopping model of charge carriers.